Renal Calculi – Pathological Research Based Homoeopathic Modality (Homoeopathy for All, 2023)
Renal calculi, also called Kidney  stones, a kidney stone is a hard,  crystalline mineral material formed  within the kidney or urinary tract.  Kidney stones are a common cause  of blood in the urine (hematuria) and  often severe pain in the abdomen,  flank, or groin. This article provides  an overview of the aetiology,  diagnosis, and appropriate general &  homoeopathic management of this  disorder.
Keywords: aetiology; hematuria; homoeopathic